OPTool - Documentation v1.2 - Silvestre, Daniel (2019)
The OPTool package is an implementation of various state-of-the-art iterative optimization algorithms for differentiable cost functions along with algorithms to solve linear equations. Users can use the toolbox to solve optimization problems, although the code was written to researchers that want to compare their proposals with state-of-the-art implementation. New algorithms can be easily added and the software will be updated to have the most comprehensive list of solvers possible. It also comes with implemented functions to return optimal parameters for these algorithms based on a control-theoretical formulation of the algorithms.